1987
DOI: 10.1002/j.1460-2075.1987.tb04791.x
|View full text |Cite
|
Sign up to set email alerts
|

The GABAA/benzodiazepine receptor is a heterotetramer of homologous alpha and beta subunits.

Abstract: The GABAA receptor has been purified to homogeneity from bovine cerebral cortex. Under stringent conditions of isolation, the GABAA receptor was shown to consist only of a (Mr 53 000) and j3 (Mr 57 000) subunits. A densitometric scan of SDS-PAGE gels under reducing conditions showed that these subunits were present in a 1:1 ratio. A model of the receptor as a heterologous tetramer x2,32 iS proposed. Monoclonal antibodies have been raised to the purified bovine GABAA receptor. One of these antibodies, 1A6, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 23 publications
8
45
0
Order By: Relevance
“…Quantitation of the gradients revealed that both proteins exhibited 9 S sedimentation coefficients, as previously described for functional GABA A receptors composed of ␣␤ or ␣␤␥ subunits (Fig. 6 A,B; Mamalaki et al, 1987Mamalaki et al, , 1989Hadingham et al, 1992;Gorrie et al, 1997;Tretter et al, 1997). In contrast, unassembled ␣ or ␤ subunits have 5 S sedimentation coefficients (Gorrie et al, 1997;Tretter et al, 1997).…”
Section: Reduced Oligomerization Of (9e10) ␣1 (Hy) With the ␤3 Subunitsupporting
confidence: 73%
See 1 more Smart Citation
“…Quantitation of the gradients revealed that both proteins exhibited 9 S sedimentation coefficients, as previously described for functional GABA A receptors composed of ␣␤ or ␣␤␥ subunits (Fig. 6 A,B; Mamalaki et al, 1987Mamalaki et al, , 1989Hadingham et al, 1992;Gorrie et al, 1997;Tretter et al, 1997). In contrast, unassembled ␣ or ␤ subunits have 5 S sedimentation coefficients (Gorrie et al, 1997;Tretter et al, 1997).…”
Section: Reduced Oligomerization Of (9e10) ␣1 (Hy) With the ␤3 Subunitsupporting
confidence: 73%
“…Together, these results demonstrate that Q67 and S68 within the ␣1 subunit are critical in mediating assembly with ␤3 to form 9S complexes, representing functional cell surface receptors (Mamalaki et al, 1987(Mamalaki et al, , 1989Hadingham et al, 1992;Gorrie et al, 1997;Tretter et al, 1997). (9E10) ␣1 (HY) subunits appear to oligomerize less efficiently with (FL AG) ␤3 compared to (9E10) ␣1 and are rapidly degraded as previously described for unassembled wild-type ␣1 subunits (Gorrie et al, 1997).…”
Section: Reduced Oligomerization Of (9e10) ␣1 (Hy) With the ␤3 Subunitsupporting
confidence: 73%
“…Three potential glycosylation sites occur at identical positions (Asn 8, 80 and 149) in the rat and bovine fl-subunit proteins. Glycosylation at any, or all of these sites (and those in the c~-subunit sequence) may account for the discrepancy between the predicted and observed Mr values of cDNA-derived [7,8] and biochemically isolated [1][2][3][4][5][6] GABAA receptor subunits, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The GABAA receptor has been purified by affinity chromatography from bovine, porcine, chick and rat brain [1][2][3][4][5]. The predominant GABAA receptor in cerebral cortex is comprised of /5'-and ~-subunit polypeptides, which bind GABA (or GABAA agonists, muscimol and isoguvacine) and benzodiazepines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-␤2 subunit antibodies recognized only two bands with M r 56,000 and 58,000 in forebrain but three to four bands in solubilized preparations of transfected HEK 293 cells. Deglycosylation of native GABA A receptor ␤2 subunits yielded two additional immunoreactive bands (39). Thus, because the ␤2 subunit is overexpressed in the HEK 293 cells, it is probable that the two additional bands are non-N-glycosylated forms of the ␤2 subunit.…”
Section: Grif-1 a Novel Gaba A Receptor-associated Proteinmentioning
confidence: 99%